Penerapan Teknik Ice Breaking pada Pembelajaran Pendidikan Agama Islam dalam Meningkatkan Hasil Belajar Siswa Kelas V di UPT SPF SD Inpres Perumnas 1 Makassar - Mardatilla Mardatilla; Abdul Fattah; Sitti Satriani (Jurnal Budi Pekerti Agama Islam, 2025)
The common problems faced by students include feeling bored, lacking concentration, and being unmotivated in learning due to the lack of collaboration among students and monotonous learning activities. Therefore, this study aims to implement ice-breaking techniques in Islamic Religious Education to improve students' learning outcomes. This research was conducted using Classroom Action Research (CAR) with two cycles, each consisting of two meetings. Each cycle followed four stages: Planning, Implementation, Observation, and Reflection. Data collection techniques included tests in the form of questions and non-test techniques such as interviews, observations, questionnaires, and documentation. Based on the results of the Classroom Action Research, it was concluded that the implementation of ice-breaking techniques in Islamic Religious Education positively influenced students' learning motivation, leading to improved learning outcomes among fifth-grade students at UPT SPF SD Inpres Perumnas 1 Makassar. The study results showed that in the pre-test, the students' average score was 68.9 (Low), with six students achieving mastery, resulting in a 30% mastery level (Low). In the first cycle, applying the ice-breaking technique to students' understanding of Islamic Religious Education resulted in an average test score of 79 (Moderate), with 13 students achieving mastery, reaching a 65% mastery level (Low). In the second cycle, the implementation of ice-breaking techniques led to an improvement in students' learning outcomes, with an average score of 89.6 (High), and 18 students achieving mastery, reaching a 90% mastery level (High). The success indicators in this study, using the Classroom Action Research (CAR) method, demonstrated an improvement in students' understanding, as evidenced by the increase in mastery learning percentages from the pre-test, first cycle, and second cycle, ultimately reaching 80% of the total number of fifth-grade students as the final learning achievement.